Advancing sustainability in low-resource settings: development and validation of a sustainability tool for evidence-based interventions and programs - Obiezu-Umeh, Chisom; Subramaniam, Divya S.; Nwaozuru, Ucheoma; Gbaja-biamila, Titilola; Blessing, Lateef Akeem; Shato, Thembekile; Oladele, David; Hirschhorn, Lisa R.; Shacham, Enbal; Xian, Hong; Ezechi, Oliver Chukwujekwu; Iwelunmor, Juliet (Frontiers in Health Services, 2025)
IntroductionDespite substantial research and growing evidence on effectiveness, the longer-term benefits of proven healthcare interventions and programs have not been fully explored due to challenges sustaining such efforts. Existing sustainability measures developed in high-income countries may not reflect determinants unique to the sustainability of interventions in low- and middle-income countries (LMICs), including African countries. To address this gap, our study developed a Sustainability Tool to Assess Evidence-Based Interventions and Programs (STEPS), which provides a theory-based measure that can be used to assess multilevel determinants of sustainability from the perspective of frontline health workers, service providers, or implementation practitioners.MethodsSTEPS domains and the initial scale item pool were generated based on a review of existing literature on sustainability in the African region. Two rounds of expert reviews were conducted with 12 experts from nine African countries, providing ratings and feedback on the relevancy of each item. Then, face validity was conducted among ten healthcare workers involved in implementing interventions and programs in Nigeria. Content validity metrics and consensus methods were used to remove redundancy, reducing the final scale to 31 items. Subsequently, we piloted STEPS among 256 healthcare workers in Nigeria directly involved in implementing evidence-based programs and/or interventions. Data were analyzed using exploratory factor analysis (EFA) to identify the underlying factor structure, followed by reliability analysis.ResultsThe EFA indicated that a four-factor 31-item structure best fits the data (Kaiser Criterion of eigenvalues >1, confirmed by scree plot, and interpretability). The four subscales are: (1) intervention characteristics (2) organizational capacity, (3) implementation context and values, and 4) socio-cultural and community context. The Cronbach's alpha for the subscales ranged from 0.83 to 0.95. Overall, STEPS demonstrated adequate content validity and excellent internal consistency for the overall scale with a Cronbach's alpha of 0.97.ConclusionOur research findings contribute to the implementation science literature by providing future researchers or programmers a means to assess factors associated with the long-term delivery and subsequent benefits of evidence-based interventions and programs in African settings. STEPS provides a context-relevant tool for assessing sustainability in the African context and other LMICs.